2023
DOI: 10.1002/inf2.12407
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput screening of phase‐engineered atomically thin transition‐metal dichalcogenides for van der Waals contacts at the Schottky–Mott limit

Abstract: A main challenge for the development of two‐dimensional devices based on atomically thin transition‐metal dichalcogenides (TMDs) is the realization of metal–semiconductor junctions (MSJs) with low contact resistance and high charge transport capability. However, traditional metal–TMD junctions usually suffer from strong Fermi‐level pinning (FLP) and chemical disorder at the interfaces, resulting in weak device performance and high energy consumption. By means of high‐throughput first‐principles calculations, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…6a, the FLP factors of several 3D and vdW-type metal–semiconductors are listed for comparison. 32 We found that the overall FLP factors decrease with increasing interfacial binding energy, indicating the increasing strength of FLP effect. In addition, the FLP factor of metal–BL PtSe 2 is smaller than that of metal–ML PtSe 2 due to the larger binding energy in metal–BL PtSe 2 , which is consistent with the overall relationship between the FLP factor and the binding energy.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…6a, the FLP factors of several 3D and vdW-type metal–semiconductors are listed for comparison. 32 We found that the overall FLP factors decrease with increasing interfacial binding energy, indicating the increasing strength of FLP effect. In addition, the FLP factor of metal–BL PtSe 2 is smaller than that of metal–ML PtSe 2 due to the larger binding energy in metal–BL PtSe 2 , which is consistent with the overall relationship between the FLP factor and the binding energy.…”
Section: Resultsmentioning
confidence: 66%
“…S3 †). 32,33 We found that the PtSe 2 -dominated bands always across the Fermi level for all the metal-PtSe 2 systems, demonstrating the hybridization of states of interfacial PtSe 2 and metals. In addition, the degree of hybridization is proportionate to the binding strength between metals and PtSe 2 .…”
Section: Band Structures and Flp Effectmentioning
confidence: 76%
See 2 more Smart Citations
“…Due to the comparable surface energies of graphene nanosheets (35-115 mJ m −2 ) and Naon lms (14.2 mJ m −2 ), the layer-by-layer structure of graphene nanosheets is easily formed. [27][28][29] By repeating the process, graphene nanosheets accumulated onto the Naon surface, and a vdWGR electrode-assisted Naon sensor (vdWGRNS) was obtained. It is worth mentioning that the thickness of the vdWGR coating cannot grow innitely because of the restriction of shear failure.…”
Section: Conformal and Highly Electrically Conductive Vdwgr Electrodesmentioning
confidence: 99%